Fabrication and characterization of micromachined piezoresistive displacement sensors - Dũng, Đinh Văn (Vietnam Journal of Science and Technology, 2012)
Summarry Silicon micromachined displacement sensors have been designed and fabricated successfully by the MEMS group at ITIMS. The structure of the sensors consists of a membrane with a stiff center. The membrane thickness is about 30 microns. The stiff center serves as a forced point and is linked to a movement system. The mechanical signal is converted into output voltage signal by a Wheatstone resistor bridge or a four-terminal gage made by diffusion on the membrane. In this paper, the configuration, fabrication process and characteristics of sensor have been presented.